Effects of red light on sleep inertia - Figueiro MG (Dove Medical Press, 2019)
Mariana G Figueiro,1 Levent Sahin,1 Charles Roohan,1 Michael Kalsher,2 Barbara Plitnick,1 Mark S Rea11Lighting Research Center, Rensselaer Polytechnic Institute, Troy, NY 12180, USA; 2Department of Cognitive Sciences, Rensselaer Polytechnic Institute, Troy, NY 12180, USAIntroduction: Sleep inertia, broadly defined as decrements in performance and lowering of alertness following waking, lasts for durations ranging between 1 min and 3 hrs. This study investigated whether, compared to a dim light condition (the control), exposure to long-wavelength (red) light delivered to closed eyelids during sleep (red light mask) and to eyes open upon waking (red light goggles) reduced sleep inertia.Methods: Thirty participants (18 females, 12 males; mean age=30.4 years [SD 13.7]) completed this crossover, within-subjects, counterbalanced design study. Self-reported measures of sleepiness and objective measures of auditory performance and cortisol levels were collected on 3 Friday nights over the course of 3 consecutive weeks.Results: Performance improved significantly during the 30-min data collection period in all experimental conditions. Subjective sleepiness also decreased significantly with time awake in all experimental conditions. As hypothesized, performance of some tasks was significantly better in the red light mask condition than in the dim light condition. Performance scores in the red light goggles condition improved significantly after a few minutes of wearing the light goggles.Discussion: The results show that saturated red light delivered through closed eyelids at levels that do not suppress melatonin can be used to mitigate sleep inertia upon waking.Keywords: sleep inertia, cognitive performance, alertness, red light, closed eyelids